More meat milk and fish—By and for the poor - Randolph, Thomas F. (International Livestock Research Institute, 2013)
Meat, milk and fish are critical to the poor both as food and income. While research has hugely increased farm production in rich countries, it hasn't succeeded yet to help the millions of family farms in developing nations to raise their production very much. The CGIAR research program on livestock and fish is experimenting with a different approach. Called ‘More meat, milk and fish by and for the poor’, it's addressing the whole way these foods move from small farms to tables. This so-called ‘food chain’ includes producing, processing, selling and consuming meat, milk and fish. The plan is within a decade to see more meat, milk and fish being produced and consumed by the people who need it most.